2001
DOI: 10.1007/s00248-001-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Epilimnetic Bacterial Community Composition, Production, and Protist-Induced Mortality along the Longitudinal Axis of a Highly Eutrophic Reservoir

Abstract: A B S T R A C TWe studied changes in the epilimnetic bacterial community composition (BCC), bacterial biomass and production, and protistan succession and bacterivory along the longitudinal axis of the canyonshaped, highly eutrophic Sau Reservoir (NE Spain) during two sampling campaigns, in April and July 1997. Longitudinal changes in BCC from the river inflow to the dam area of the reservoir were detected by using oligonucleotide probes targeted to the kingdom Bacteria, to the alpha, beta, and gamma subclasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
7
41
0
2
Order By: Relevance
“…These mechanisms are assumed to include a large scale sedimentation (Grimason et al 1993), as was confirmed by the presence of the pathogens in the sediment. Table 2 and/or invertebrates (Fayer et al 2000;Simek et al 2001;Stott et al 2001). Overall, the removal of G. lamblia was greater than that of C. parvum, comparing well with literature.…”
Section: Removal Rates and Mechanismssupporting
confidence: 82%
“…These mechanisms are assumed to include a large scale sedimentation (Grimason et al 1993), as was confirmed by the presence of the pathogens in the sediment. Table 2 and/or invertebrates (Fayer et al 2000;Simek et al 2001;Stott et al 2001). Overall, the removal of G. lamblia was greater than that of C. parvum, comparing well with literature.…”
Section: Removal Rates and Mechanismssupporting
confidence: 82%
“…Statistical evaluations of DGGE patterns have shown correlations to the grazer abundance in several lake studies (Lindström 2000(Lindström , 2001Muylaert et al 2002). Also, in experimental studies, it has been shown that grazers are capable of shaping bacterioplankton assemblage composition (e.g., Simek et al 1997;Hahn and Höfle 1998;Gasol et al 2002). Therefore, differences in grazing pressure may also have had some influence on the differences in bacterioplankton communities between lakes and inlets.…”
Section: Discussionmentioning
confidence: 99%
“…That such factors also may influence the composition of bacterial assemblages is likely (e.g., Methé and Zehr 1999;Simek et al 2001a;Lindström and Leskinen 2002;Muylaert et al 2002;Crump et al 2003;Stepanauskas et al 2003). Here we show that the import of the bacteria themselves also may contribute to the structure of lake bacterioplankton assemblages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds et al (2002) realized that this influence is strong enough to allow functional classification of phytoplankton largely on the basis of characteristics of the physical environment. Moreover, spatial and temporal variability of ecological processes in lakes and the ocean have been associated with a wide range of physical processes: longitudinal shear dispersion (Okubo 1980;Martin 2003), vertical shear dispersion (Martin 2003;Cowles 2004), internal wave oscillations (Franks 1995), wind-induced upwelling (Robarts et al 1998), internal wave breaking (MacIntyre et al 1999), and buoyancy-driven inflows (Serruya 1974;Š imek et al 2001), to name a few. In man-made lakes, the water quality and ecology is often regulated by the characteristics of the inflowing rivers carrying nutrients and organic matter into a lake Friedl and Wü est 2002;Masin et al 2003).…”
mentioning
confidence: 99%